(3ebOeI (B-(3GdfXQjI GdYGeI ddTQcGJ TQcGJ GdCTNGUs - (3SGej YHO GdHGbj(B, (3CHh UGdMs ((3GdbGgQI(B:s (3OGQ GdfgVI GdYQHjI(B,s, 2003)
(3GdfXQjI GdYGeI ddTQcI, GdTQcI cYbO, GdCQcGf GdehVhYjI GdYGeI dYbO GdTQcI, GdQcf GdKGdK, GdCQcGf GdehVhYjI GdNGUI dYbO GdTQcI, GdCQcGf GdJTcjdjI dYbO GdTQcI, BKGQ JNda Ch JZjjH CQGcf YbO GdTQcI, GdTQcI cTNU eYfhj, HOA GdTMUjI GdeYfhjI ddTQcI hfgGjJgG, fJGFL GcJSGH GdTQcI ddTNUjI GdeYfhjI, CSHGH GfbVGA GdTQcI, BKGQ GfbVGA GdTQcI, TQcGJ GdCTNGU, TQcI GdJVGef, TQcI GdJhUjI GdHSjWI, TQcI GdeMGUdI(B.s
Keywords: (3GdSfOGJs; (3GdTQcGJs